Pediatric acute asthma scoring systems: a systematic review and survey of UK practice. Issue 5 (2nd June 2020) - Chacko, Jerry; King, Charlotte; Harkness, David; Messahel, Shrouk; Grice, Julie; Roe, John; Mullen, Niall; Sinha, Ian P.; Hawcutt, Daniel B.; ,
Abstract: Background: Acute exacerbations of asthma are common in children. Multiple asthma severity scores exist, but current emergency department (ED) use of severity scores is not known. Methods: A systematic review was undertaken to identify the parameters collected in pediatric asthma severity scores. A survey of Paediatric Emergency Research in the United Kingdom and Ireland (PERUKI) sites was undertaken to ascertain routinely collected asthma data and information about severity scores. Included studies examined severity of asthma exacerbation in children 5–18 years of age with extractable severity parameters. Results: Sixteen articles were eligible, containing 17 asthma severity scores. The severity scores assessed combinations of 15 different parameters (median, 6; range, 2–8). The most common parameters considered were expiratory wheeze (15/17), inspiratory wheeze (13/17), respiratory rate (10/17), and general accessory muscle use (9/17). Fifty‐nine PERUKI centers responded to the questionnaire. Twenty centers (33.1%) currently assess severity, but few use a published score. The most commonly recorded routine data required for severity scores were oxygen saturations (59/59, 100%), heart rate, and respiratory rate (58/59, 98.3% for both). Among well‐validated scores like the Pulmonary Index Score (PIS), Pediatric Asthma Severity Score (PASS), Childhood Asthma Score (CAS), and the Pediatric Respiratory Assessment Measure (PRAM), only 6/59 (10.2%), 3/59 (5.1%), 1/59 (1.7%), and 0 (0%) of units respectively routinely collect the data required to calculate them. Conclusion: Standardized published pediatric asthma severity scores are infrequently used. Improved routine data collection focusing on the key parameters common to multiple scores could improve this, facilitating research and audit of pediatric acute asthma.